Sildenafil does not reliably improve exercise performance in hypoxia: a systematic review. Issue 1 (29th March 2019) - Carter, Eric Alexander; Lohse, Keith; Sheel, William; Koehle, Michael
Abstract : Objective: Sildenafil is a pulmonary vasodilator that may reduce the decrement in endurance performance in moderate hypoxia. We assessed the efficacy of sildenafil to improve performance in hypoxia. Data sources/eligibility Criteria: We systematically searched electronic databases (until August 2018) for randomised trials comparing sildenafil with placebo. We also examined the effect of sildenafil on pulmonary artery pressure (PAP), cardiac output (CO) and pulse oxygen saturation (SP O2 ) compared with placebo in hypoxia. Fourteen studies were included; 210 subjects received sildenafil 40, 50 or 100 mg/day. Results: Sildenafil showed a large effect for decreasing PAP during exercise and at rest, a small effect for increasing CO during exercise and a moderate effect at rest, a moderate effect for increasing SP O2 and a small effect for improving performance. In a subgroup analysis, there was no statistically significant difference between 100 and 50 mg sildenafil dose on SP O2 . Sildenafil had a moderate effect on increasing SP O2 and performance at terrestrial hypobaric altitude but only a small effect on both in normobaric hypoxia. Regression analysis showed that hypoxic dose (PO2 ) and metabolic rate do not account for a significant portion of the variance in effect size for sildenafil on PAP, CO, SP O2 and performance. Conclusion: This meta-analysis indicates that sildenafil reduces PAP, has a moderate to small effect on CO and SP O2, and no effect on performance.